(untitled) (Papeles, 2022)
Introduction: This article describes the findings related to Economics teaching practices that were the result of the research. The aim of the research was to characterize and understand the didactic, pedagogical, and institutional aspects of those practices. Methodology: With the support provided by critical didactics, the characteristics of economics as a discipline and the qualitative research methodology, supported by the case study method, aspects inherent to the teaching practices of economics in context were addressed. Semi-structured interviews with teachers of the Economics Department of the Universidad Nacional de Sur, non-participant classroom observations, document analysis and brief interviews with other key actors were used. Results and discussion: Based on the action in the field and the empirical findings, types and modalities of economics teacher were constructed. Conclusions: Finally, a dialogue is opened to reflect and think about teaching of economics at the university level.